2017
DOI: 10.1002/mus.26007
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain due to superior cluneal nerve entrapment: A clinicopathologic study

Abstract: The pathologic findings and effectiveness of neurectomy suggest that, in our patients, SCN neuropathy likely elicited LBP via nerve compression. Muscle Nerve 57: 777-783, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The SCN originates from the lower thoracic and lumbar spinal nerves, passes through the thoracolumbar fascia, and can be entrapped at the penetrating orifice of the thoracolumbar fascia [4,14]. The anatomic and functional bases for the development of SCN-EN include a rigid fascial edge and stretching of the gluteus maximus muscle and skin over a large area during flexion of the hip joint [6,16,17]. Several reports have suggested that 1.6%–14.0% of all cases of LBP involve SCNEN [5,8,15].…”
Section: Discussionmentioning
confidence: 99%
“…The SCN originates from the lower thoracic and lumbar spinal nerves, passes through the thoracolumbar fascia, and can be entrapped at the penetrating orifice of the thoracolumbar fascia [4,14]. The anatomic and functional bases for the development of SCN-EN include a rigid fascial edge and stretching of the gluteus maximus muscle and skin over a large area during flexion of the hip joint [6,16,17]. Several reports have suggested that 1.6%–14.0% of all cases of LBP involve SCNEN [5,8,15].…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, we reported that superior/middle cluneal nerve entrapment around the iliac crest can elicit LBP; the symptoms are similar to LBP due to coexisting lumbar disease [22,23] whose clinical and pathological features are those of peripheral nerve neuropathy [23]. Neuropathic pain from these diseases may be alleviated by mirogabalin.…”
Section: Effects Of Mirogabalin On Low Back Painmentioning
confidence: 96%
“…7 Though histopathologic evidence on CN is lacking, one pathological study on 2 patients s/p SCN-neurectomy revealed thickened perineurium, subperineurial edema, Renaut bodies, and nerve enlargement related to an increase in thinly myelinated fibers, which paralleled findings in other studies as well. [8][9][10][11][12][13] This sheds some light on the microanatomical considerations on cluneal neuralgia, but more literature exists on SCN-e and MCN-e on a macroscopic level. In the following paragraphs, we investigate the anatomy of the SCN and its described pathophysiologies, followed by that of the MCN, and conclude with a brief investigation of risk factors and possible associations relating to, and causing, cluneal neuralgia.…”
Section: Pathophysiology/risk Factorsmentioning
confidence: 99%